Hypertrophic cardiomyopathy without hypertrophy: two families with myocardial disarray in the absence of increased myocardial mass. - McKenna, W J (1990)
Two families are described in which individuals showed widespread myocardial disarray at histological examination, in the absence of macroscopic cardiac hypertrophy. In one family the clinical presentation was that of sudden unexpected cardiac death in four family members; members of the other family presented with electrocardiographic repolarisation changes and abnormalities of left ventricular diastolic function. The finding of myocardial disarray, the characteristic histological abnormality of hypertrophic cardiomyopathy, in the absence of increased cardiac mass suggests a wider range of abnormality in hypertrophic cardiomyopathy than is currently recognised.